2011
DOI: 10.1007/s00382-011-1234-7
|View full text |Cite
|
Sign up to set email alerts
|

Change in the precipitation intensity of the East Asian summer monsoon projected by CMIP3 models

Abstract: Future change in precipitation intensity of East Asian summer monsoon is investigated using the present-day climate simulations (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000) and the future climate simulations (2091-2100, A1B emission scenario) by the Couple Model Intercomparison Project 3 (CMIP3) models. Target period is the month from June to July which is the main part of the rainy season over Japan and Korea. In the present-day climate simulations, we have quantitatively evaluated model's rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 29 publications
2
40
0
1
Order By: Relevance
“…It should be noted that the present climatological summer monsoon rainband from East China to Japan is underestimated by BCC_CSM1.1 (Fig. 10e), which is a bias common to most climate models (Kusunoki and Arakawa 2012). This increases the uncertainty of the precipitation change projected under the RCPs.…”
Section: Atmospheric Circulationmentioning
confidence: 96%
“…It should be noted that the present climatological summer monsoon rainband from East China to Japan is underestimated by BCC_CSM1.1 (Fig. 10e), which is a bias common to most climate models (Kusunoki and Arakawa 2012). This increases the uncertainty of the precipitation change projected under the RCPs.…”
Section: Atmospheric Circulationmentioning
confidence: 96%
“…Kang et al (2002) showed Atmospheric General Circulation Model (AGCM)s underestimate precipitation amount of the Baiu rain band and fail to reproduce the Baiu season. Kusunoki and Arakawa (2012) also indicated most of Atmospheric-Ocean General Circulation Model (AOGCM)s of Coupled Model Intercomparison Project phase 3 (CMIP3) underestimate precipitation amount of the Baiu rain band. Models with higher horizontal resolution in atmosphere improve the reproducibility of the Baiu rain band compared with low resolution models Kusunoki et al 2011, hereafter referred to as K2011).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, atmospheric general circulation models (AGCMs) are the most advanced tools for global climate simulations and projections (Oouchi et al 2006;Anandhi et al 2008;Kusunoki and Arakawa 2012). However, they are unable to well capture local features that are induced by topography and mesoscale disturbances.…”
Section: Introductionmentioning
confidence: 99%